2011
DOI: 10.1007/s10886-011-9943-2
|View full text |Cite
|
Sign up to set email alerts
|

Lysophospholipids in the Mediterranean Sponge Oscarella tuberculata: Seasonal Variability and Putative Biological Role

Abstract: Lysophospholipids (LPLs) are recognized as important signaling molecules in metazoan cells. LPLs seem to be widely distributed among marine invertebrates, but their physiological role remains poorly known. Marine sponges produce original phospholipids and LPLs whose isolation and structural elucidation rarely have been reported. Two LPLs were isolated for the first time from the Mediterranean Homoscleromorph sponge Oscarella tuberculata: a bioactive lyso-PAF already identified in some other sponge species; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…This limited intraspecific metabolic variability observed between the two locations might be related to the genetic diversity as previously suggested [1,33,54,55,56,57]. In accordance with previous studies [13,14,15,20,23,58], a marked seasonal trend of the metabolic content showed a maximum in autumn and a minimum in spring (specimens of the Ligurian Sea, Figure 2). Interestingly, the same seasonal pattern was observed in both wild and farmed specimens cultured in this area, suggesting a role of internal physiological factors as main drivers of the variations of the specialized metabolism.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This limited intraspecific metabolic variability observed between the two locations might be related to the genetic diversity as previously suggested [1,33,54,55,56,57]. In accordance with previous studies [13,14,15,20,23,58], a marked seasonal trend of the metabolic content showed a maximum in autumn and a minimum in spring (specimens of the Ligurian Sea, Figure 2). Interestingly, the same seasonal pattern was observed in both wild and farmed specimens cultured in this area, suggesting a role of internal physiological factors as main drivers of the variations of the specialized metabolism.…”
Section: Discussionsupporting
confidence: 90%
“…Since spatial and temporal variations in concentrations of major specialized metabolites have been documented previously [13,14,15], the ideal farming location that promotes their biosynthesis as well as the harvest season have to be assessed. The natural variations in the production of the specialized metabolites have been mostly explained by environmental and ecological factors like biotic interactions [16,17,18,19], abiotic factors [13,20,21,22] or more rarely, the organism’s life cycle [15,23] as well as physiological state [24,25]. Overall, the effects of abiotic factors on the production of specialized metabolites have produced contrasting results so far [20,26,27,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the production of defensive compounds may also be influenced by several abiotic factors such as temperature (Ivanisevic et al 2011b;Reverter et al 2016), light (Cronin and Hay 1996;Deneb 2001;Paul 2006), and nutrient availability (Cronin and Hay 1996). Moreover, internal factors such as reproductive stage (Ivanisevic et al 2011a;Vergés et al 2008), ontogeny ) are globally subjected to seasonal variation and consequently they may affect the s pecialized metabolism ( Ivanisevic et al 2011a). …”
Section: Introductionmentioning
confidence: 99%
“…In particular, phospholipids as important membrane constituents of biological vesicles are commonly involved in delineating reaction compartments for the crystallization of biominerals (e.g., Gorby et al 1988;Collier and Messersmith 2002;Bäuerlein 2003;Anderson et al 2005). The isolation and structural determination of phospholipids from biosilicification organisms including sponges and diatoms have been reported (e.g., Djerassi and Lam 1991;Early et al 1996;Genin et al 2008;Ivanisevic et al 2011). For example, the sponge cell membrane is unique in terms of its lipid diversity, and Ivanisevic et al (2011) suggest that lysophospholipids could play an important role in sponge embryogenesis and morphogenesis.…”
mentioning
confidence: 99%
“…The isolation and structural determination of phospholipids from biosilicification organisms including sponges and diatoms have been reported (e.g., Djerassi and Lam 1991;Early et al 1996;Genin et al 2008;Ivanisevic et al 2011). For example, the sponge cell membrane is unique in terms of its lipid diversity, and Ivanisevic et al (2011) suggest that lysophospholipids could play an important role in sponge embryogenesis and morphogenesis. Phospholipid membrane was also found to surround hexactinellid spicules and delimit the confined space where silicification occurs (Uriz 2006).…”
mentioning
confidence: 99%